Building Community Resilience Through the Preservation of Fitrah and Strengthening Socio-Spiritual Family Integration: A Sufi Perspective - Derosi Zakiyah, Ade Rosi Siti Zakiah; Muhammad Nasiruddin, Muhammad Nasiruddin; Abdul Rohman, Abdul Rohman (Universitas Islam Negeri Raden Intan Lampung, 2025)
Community resilience has become an important issue in facing various social, economic, and cultural challenges in the modern era. This paper aims to analyze how the perspective of Sufism can contribute to efforts to build community resilience through two main approaches: the preservation of human fitrah (innate nature) and the strengthening of socio-spiritual family bonds. This study is based on the understanding that humans possess a sacred and noble fitrah, but it is often uprooted from its natural state due to various negative influences. The preservation and restoration of humans to their fitrah are believed to be crucial foundations for strengthening community resilience. Additionally, the family, as the smallest unit in society, also plays a strategic role in building resilience, especially through strengthening social and spiritual bonds among family members. This research uses a literature review approach to analyze Sufi concepts related to the preservation of human fitrah and the strengthening of socio-spiritual family integration. Sufi anthropological theory and socio-spiritual Sufi theory are used as conceptual frameworks in analyzing the data. The study results indicate that the Sufi perspective offers a holistic paradigm in understanding humans and families, placing spiritual aspects as the foundation for strengthening the social dimension. Through the preservation of fitrah and the strengthening of socio-spiritual family bonds, it is hoped that a more resilient, harmonious, and spiritually-oriented society can be fostered.